Parent emotion regulation difficulties statistically mediate the association between parental adverse childhood experiences and child emotion regulation - Freeman, Sarah E.; Staples, Angela D.; Loverich, Tamara M.; Hannapel, Madison; Lawler, Jamie M. (Frontiers in Global Women's Health, 2025)
IntroductionEmotion regulation (ER) abilities predict positive outcomes among children. While parenting behaviors that promote young children's ER development have been widely studied, less is known about how a parent's history of early trauma may interfere with their use of effective strategies, despite well-documented next-generation impacts of early adversity. The present study evaluates the statistical mediating role of parent ER and parent emotion-related socialization behaviors (ERSBs) in the relation between parent adverse childhood experiences (ACEs) and child ER.MethodsData come from a cross-sectional study of 214 caregivers of children ages 2 through 5 (inclusive) participating in a larger online study examining parenting factors that are associated with children's self-regulation development. Measures used include Traditional and Expanded ACEs Scales, the Difficulties in Emotion Regulation Scale Short Form, the Coping with Toddlers' Negative Emotions Scale, and the Emotion Regulation Checklist. Data analysis involved correlation and mediation analyses.ResultsParent difficulties in ER statistically mediated the association between parent ACEs and child ER such that a higher expanded ACEs score was associated with more parent difficulties in ER, and these difficulties were related to lower child ER. Although parent ER and emotion-accepting ERSBs independently contribute to child ER, data did not support a statistical mediational role for ERSBs or multiple statistical mediation.DiscussionStudy findings implicate parent ER as a potential target for parenting interventions aiming to promote child ER among parents with a history of adversity, suggesting that support for parent ER may be one avenue for the reduction of intergenerational transmission of trauma.